TCP - Barakat, C.
We discuss the different issues to be considered when modeling the TCP protocol in a real environment. The discussion is based on measurements we made over the Internet. We show that the Internet is so heterogeneous that a simplistic assumption about TCP congestion control or the network may lead to erroneous results. We outline some of our results in this field, and we present a novel approach For a correct validation of a model for TCP
Keywords: Internet; TCP congestion control; TCP protocol; TCP window evolution; TCP/IP modeling; TCP/IP validation; Measurement testbed; Network modelling